2009
DOI: 10.1007/s00216-009-3217-7
|View full text |Cite
|
Sign up to set email alerts
|

Human breath analysis: methods for sample collection and reduction of localized background effects

Abstract: Solid-phase microextraction (SPME) was applied, in conjunction with gas chromatography-mass spectrometry, to the analysis of volatile organic compounds (VOCs) in human breath samples without requiring exhaled breath condensate collection. A new procedure, exhaled breath vapor (EBV) collection, involving the active sampling and preconcentration of a breath sample with a SPME fiber fitted inside a modified commercial breath-collection device, the RTube, is described. Immediately after sample collection, compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 60 publications
0
54
0
1
Order By: Relevance
“…EBC contains both volatiles and non-volatiles, and these must be recognized as separate entities with different properties [34]. But, it has been found that conventional EBC-collection methods (e.g., Rtube at -80ºC) yield significantly lower sensitivity in the analysis of VOCs than specific EBV-concentration methodologies {e.g., solid-phase microextraction (SPME) [35]}. When VOCs are the analytes of interest, EBV sampling is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…EBC contains both volatiles and non-volatiles, and these must be recognized as separate entities with different properties [34]. But, it has been found that conventional EBC-collection methods (e.g., Rtube at -80ºC) yield significantly lower sensitivity in the analysis of VOCs than specific EBV-concentration methodologies {e.g., solid-phase microextraction (SPME) [35]}. When VOCs are the analytes of interest, EBV sampling is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…However, an ATS/ERS task force addressed several issues resulting in novel EBC guidelines [85]. Several collectors and condensers are currently available [86][87][88][89][90]. All devices are easy to use and subsequent exhaled breath collection can be simply obtained from both young and elderly individuals.…”
Section: Exhaled Breath Condensate (Ebc)mentioning
confidence: 99%
“…This method is currently applied in MS breath analysis by measuring the metabolic concentration in volatiles (also in EBCs) and subtracting (filtering) the analytes from room air. Details about room air measurement have been previously reported [14]. A similar approach cannot be easily translated to NMR-based metabolomic data.…”
Section: To the Editorsmentioning
confidence: 99%